Imagined truths : realism in modern Spanish literature and culture - Coffey, Mary L., 1956-; Versteeg, Margot (Toronto Iberic, 2019)
"This volume of scholarly essays brings together the work of the foremost specialists in the field of contemporary Spanish letters. It represents not only the first collection to focus exclusively on the phenomenon of realism within the context of modern Spanish literature in more than a quarter century, but also the first to be written in English. Imagined Truths appears at a significant moment of renewed interest in realism as a literary, historical, and cultural phenomenon. The essays in this collection address a broad range of authors, works, and topics from an exploration of the continued relevance of Cervantes' Don Quixote to Juan Marse's twenty-first century detective fiction, and they focus on the various ways in which we understand and process narratives as representative of a certain kind of reality. In addition to their valuable analyses of particular works and authors, the essays constitute a much-needed scholarly dialogue that expands our understanding of the unique place of realism in Spain's cultural history."--